Exploring situated expectancy-value theory: a study of gendered higher education choices - Pikić Jugović, Ivana; Doolan, Karin; Baranović, Branislava (Psihološka istraživanja, 2024)
The article examines how motivational beliefs, gender roles and stereotypes, as well as cultural resources and practices shape students’ choices of university courses in the technical sciences and the social sciences and humanities. Its theoretical backbone is Eccles et al.’s situated expectancy-value theory, with an emphasis on the importance of its gender dimension, as well as sociocultural background as expressed through cultural capital indicators. Questionnaire data were collected from 1301 high school students in Croatia. Results show that motivational beliefs, especially utility values, were the strongest predictors of study choice for both young women and men. Traditional gender roles predicted weaker intentions to choose gender non-stereotypical courses. Endorsing gender stereotypes about a lesser talent of one’s own gender for occupations in the technical sciences or social sciences and humanities predicted weaker intentions to choose courses in those fields of study. Finally, reading practices, as an indicator of cultural capital, added to the explanation of social science and humanities course choices for both young women and men. The implication of the research is the need to create intervention programmes aimed at deconstructing gender roles and challenging pupils’ stereotypes about educational domains and occupations.
Keywords: Situated expectancy-value theory, Educational choices, Gender, Motivation, High school pupils